Territorial barriers in urban environments: Conceptualisation of the term and assessment methodology (case study of the central area of Perm) - Volkov, Stanislav Andreevich; Merkushev, Sergey A.; Tarantin, Mikhail Romanovich (Известия Саратовского университета. Новая серия: Серия Науки о Земле)
Introduction. This study focuses on the examination of territorial barriers in urban environments. It analyses the main types of barriers, their role in the spatial development of the city, and their impact on the formation of socio-economic interactions. Data and Methods. A methodology for calculating the permeability coefficient of territorial barriers has been developed. This methodology is based on a combination of objective criteria (accessibility, traversability) and subjective evaluations (type of crossing, accessibility, isolation, type of surface, surface quality). Results and Discussion. The methodology was tested using segments of the boundary of the central area of Perm. Calculations confirmed the highest permeability of contact boundaries, which primarily serve as nominal demarcation lines. Restrictive and divisive boundary segments show varying degrees of barrier effects depending on the level of infrastructural development. Problematic segments are characteristic of zones with changing functions. Conclusions. The proposed methodology allowed for a more objective characterisation of boundary types, clarification of their functional features, and the development of recommendations for altering specific boundary segments. For instance, segments near Chernyaevsky Forest Park and the Solovyov Garden were recommended to be designated as contact boundaries.